Training Transfer and Psychological Empowerment on Job Performance Mediating Role of Organizational Commitment - Keke Tamara Fahira; Nurzahroh Lailyah; Tina Rahayu (MEC-J (Management and Economics Journal), 2022)
Organizational succession can be determined by stable and significant work performance. The low work performance of employees due to the quality of training transfers that are less than optimal is the reason for this study. This study aims to analyze the effect of transfer of training and psychological empowerment that can affect the improvement of work performance through organizational commitment. The sample used is all staff-level employees at PT. BRI Life Insurance Semarang Regional Office, totaling 150 employees. Sampling using purposive sampling technique with AMOS SEM data analysis technique. The results showed that job performance can be influenced by the transfer of training and psychological empowerment through organizational commitment. From the results of the study, it can be concluded to improve work performance at PT. BRI Life Insurance Semarang Regional Office can be pursued by paying attention to and increasing the success of the transfer of training and psychological empowerment because they are important things and have been emphasized in this study.